Forecasting of the number of air passengers in the United States in terms of the maintenance of economic security during the impact of COVID-19 - Kozicki, Bartosz; Britchenko, Igor; Ovsepyan, Arsen; Grabowska, Sabina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The purpose of the study is to forecast the number of passengers transported by air in the United States for 2021-2022. The forecast is preceded by a multidimensional comparative analysis of the number of passengers transported by air in the United States from 1 January 2019 to 2 November 2021. To achieve this goal, the research data were grouped as dependent variables: years, months-years. The observed similarities, the analysis and evaluation of the literature as well as our own experience made it possible to forecast primary data for the future. The obtained results show a growing trend in the number of passengers transported by air in the United States. The forecast for 3 November 2021 to 31 December 2022 is 837,459, 877 prospective air passengers in the United States. The standard deviation of the obtained forecast was 255,680,3, the arithmetic mean was 1,975,141 passengers, and the median was 1,998,478 passengers. The observed similar trends in the identical months of July-October in 2019 and 2021 as well as the analysis of the literature and the own experience allowed for the selection of a method for the forecasting of the number of passengers transported by air in the United States for the future. The detected regularities as recurring trends in the number of air passengers transported in the United States on a dynamic basis may be used to forecast them for the future.

Celem badania jest prognoza liczby pasażerów przewiezionych drogą lotniczą w Stanach Zjednoczonych na lata 2021-2022. Prognozę poprzedza wielowymiarowa analiza porównawcza liczby pasażerów przewiezionych drogą lotniczą w Stanach Zjednoczonych od 1 stycznia 2019 r. do 2 listopada 2021 r. Aby osiągnąć ten cel, dane pogrupowano jako zmienne zależne: lata, miesiące-lata. Zaobserwowane podobieństwa, analiza i ocena literatury oraz własne doświadczenia pozwoliły na prognozowanie danych pierwotnych na przyszłość. Uzyskane wyniki wskazują na rosnący trend liczby pasażerów przewożonych drogą lotniczą w Stanach Zjednoczonych. Prognoza na okres od 3 listopada 2021 do 31 grudnia 2022 to 837 459 877 potencjalnych pasażerów lotniczych w Stanach Zjednoczonych. Odchylenie standardowe uzyskanej prognozy wyniosło 255 680,3, średnia arytmetyczna 1 975 141 pasażerów, a mediana 1 998 478 pasażerów. Obserwowane podobne trendy w identycznych miesiącach lipiec-październik w 2019 i 2021 roku oraz analiza literatury i własnych doświadczeń pozwoliły na wybór metody prognozowania liczby pasażerów przewiezionych drogą lotniczą w Stanach Zjednoczonych na przyszłość. Wykryte prawidłowości jako powtarzające się trendy w liczbie pasażerów lotniczych przewożonych w Stanach Zjednoczonych na zasadzie dynamicznej mogą posłużyć do ich prognozowania na przyszłość.
Keywords: economic security; air transport; forecasting; data analysis; COVID-19 pandemic; bezpieczeństwo ekonomiczne; transport lotniczy; prognozowanie; analiza danych; pandemia COVID-19